2016
DOI: 10.1002/jbm.b.33705
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hypoxia on thermosensitive poly(N -vinylcaprolactam) hydrogels with tunable mechanical integrity for cartilage tissue engineering

Abstract: Cartilage repair presents a daunting challenge in tissue engineering applications due to the low oxygen conditions (hypoxia) affiliated in diseased states. Hence, the use of biomaterial scaffolds with unique variability is imperative to treat diseased or damaged cartilage. Thermosensitive hydrogels show promise as injectable materials that can be used as tissue scaffolds for cartilage tissue regeneration. However, uses in clinical applications are limited to due mechanical stability and therapeutic efficacy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Another studied synthetic‐natural hydrogel system was poly( N ‐vinylcaprolactam) (PVCL)‐ g ‐HA. PVCL was used as an alternative thermogel to p(NIPAAm) . Despite suitable LCST around 33°C, their mechanical properties (storage modulus: 7 Pa, loss modulus: 4 Pa) were much lower than moduli of native cartilage.…”
Section: Injectable Hydrogels In Cartilage Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Another studied synthetic‐natural hydrogel system was poly( N ‐vinylcaprolactam) (PVCL)‐ g ‐HA. PVCL was used as an alternative thermogel to p(NIPAAm) . Despite suitable LCST around 33°C, their mechanical properties (storage modulus: 7 Pa, loss modulus: 4 Pa) were much lower than moduli of native cartilage.…”
Section: Injectable Hydrogels In Cartilage Engineeringmentioning
confidence: 99%
“…Based on the literature review, it can be stated, that mechanical properties are the biggest challenge in the application of hydrogels in cartilage repair. Studied thermogels have properties differing by several orders of magnitude, for example (PVCL)‐ g ‐HA—storage modulus 7 Pa, carboxymethyl chitin: 250 Pa, PEG‐polyalanine: 844 Pa, polyalanine–poloxamer–polyalanine, about 1500 Pa, but still much lower in comparison to native cartilage (human cartilage storage modulus: 32/43 MPa) …”
Section: Injectable Hydrogels In Cartilage Engineeringmentioning
confidence: 99%
“…Apart from mechanical properties, synthetic polymers can have versatile functions. Poly(N-vinylcaprolactam) (PVCL) is a cytocompatible thermosensitive polymer that can be used to fabricate injectable hydrogels for cartilage tissue engineering [ 42 , 43 ]. Sala et al showed chondrocytes and MSCs exhibited high viability in PVCL hydrogels [ 42 ].…”
Section: Current State-of-art Of Hydrogels Designed For Cartilage Regmentioning
confidence: 99%
“…Polymer molecular weight can affect LCST. Because of its biocompatibility and low cytotoxicity, PVCL is considered an ideal thermoresponsive polymer for biomedical applications [ 97 , 98 , 99 ], particularly when compared to PNIPAM [ 100 , 101 , 102 ]. PVCL conjugation with hydrophilic units such as PEG or derivatives of PEG enables the synthesis of temperature-responsive block copolymers.…”
Section: Thermosensitive Polymersmentioning
confidence: 99%